(R)-4-Isopropyl-3-isopropylsulfanyl-5,5-diphenyl-1,3-oxazolidin-2-one - Gustavo Pozza Silveira; Cassandra Bonfante de Carvallho; Allen Oliver (Acta Crystallographica Section E, 2012)
The title compound, C21H25NO2S, consists of a five-membered heterocyclic ring, with pendant phenyl groups, an isopropyl group and a thioether residue. The thioether bonds to the heterocycle via the N atom. The absolute configuration results from an inversion of the configuration of substrate during the synthesis.